ImageLogViewer: An open-source solution for exploring images from micro-resistivity and ultrasonic boreholes - Piva, Rodrigo; A. Cruz, Matheus; Braga, Paola; Dias, Rodrigo; Siqueira, Paulo; A. Trevizan, Willian; M. de Jesus, Candida; M. Souza, André; Salvador, Rodrigo; Fernandes, Leandro; C. Bernardini, Flávia; Sousa, Elaine P. M. de; et al. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2024)
Borehole image logs are critical for characterizing reservoirs in the petroleum industry. Exploring this data is challenging because image logs are extensive in size and demand multiple measurements to be juxtaposed side-by-side, such as resistivity and acoustic data. Despite its importance, no open-source applications exist to analyze such data. In this demonstration, we present ImageLogViewer, a Python-based tool for visualizing image logs. It can simultaneously display acoustic and dynamic/static micro-resistivity data with multiple display modes and custom windowing to facilitate the analysis of structures, e.g., fractures and cavities. It also integrates image processing, machine, and deep learning models for classifying and segmenting regions of interest.